Does government behaviour or enterprise investment improve regional innovation performance? - evidence from China. (14th May 2021) - Zheng, Ye; Han, Wei; Yang, Ruoyu
Whether government behaviour or enterprise investment promotes regional innovation performance more effectively remains unclear. This study empirically analyses Chinese panel data from 2008 to 2016 and examines the influences of the determination of high and new technology enterprises, enterprise R&D investment, and institutional environment on regional innovation performance. The results indicate that the determination of high and new technology enterprises has a limited positive effect on regional innovation performance, whereas enterprise R&D investment has a mostly positive significant effect. Furthermore, the institutional environment has a positive moderating effect on enterprise R&D investment relationships and a negative moderating effect on tax burden relationships. Moreover, all these relationships are affected by locational factors, particularly in the eastern region. Based on these findings, this study proposes corresponding policy suggestions.